Effect of Vitamin D Supplementation on Regulatory T Cells of Systemic LupusErythematosus: A Systematic Review - Yuniza Yuniza (Indonesian Rheumatology Associantion, 2023)
Background. Systemic lupus erythematosus (SLE) is associated with aglobal reduction in regulatory T cells (Tregs). Vitamin D supplementationthat is efficacious, safe, and reasonably priced has the potential to reducemorbidity in SLE. This study was aimed to systematically assess the efficacyof vitamin D supplementation in enhancing Tregs concentration or Tregsrelated marker. Methods. A systematic review of the literature for clinicalstudies was performed on Pubmed, Proquest, and Google Scholar. Studieswere assessed for risk of bias using Newcastle Ottawa Scale. All clinicalstudies that investigated the effects of vitamin D supplementation on Tregsin SLE patients were included. Key evidence was analyzed and qualitativelysynthesized. Results. Three relevant studies were included. All studies wereof high-quality. Vitamin D supplementation consistently increased Tregsconcentration across all included studies. Conclusion. The current studysupports the evidence that vitamin D supplementation enhanced Tregsconcentration in SLE patients.